Islamic Banking and Economic Growth: A Case Study in Indonesia - Hikmah, Lailatul; Hafizhah, Nur Zakiya; Rusgianto, Sulistya (Islamic Family Law Department, STAI Syekh Abdur Rauf Aceh Singkil, Indonesia, 2025)
This research analyzes the influence of total assets, total financing, and total sharia banking deposits on economic growth in Indonesia, as measured by Gross Domestic Product (GDP). Secondary data is used from the first quarter of 2015 to the last quarter of 2023, using the Vector Error Correction Model (VECM) method to identify long-term and short-term relationships between these variables. The research results show that total Islamic banking assets have a positive and significant effect on GDP in the long term, but have a negative effect in the short term. Total financing does not show a significant effect in the short term and even has a negative impact in the long term. On the other hand, total deposits have a significant positive effect on GDP in the long term. These findings highlight the importance of efficiency in asset management and Sharia banking financing as well as the need for policies that support stability and public trust in Sharia banking. The contribution of this research lies in providing empirical evidence regarding the role of Islamic banking in Indonesia's economic growth, especially through the analysis of the long-term and short-term relationship between total assets, total financing, and total deposits to GDP. These findings enrich the literature regarding the effectiveness of sharia banking in the national financial system and provide implications for policies aimed at increasing the efficiency of asset management and sharia financing. In addition, this research provides insight for regulators and banking practitioners in designing strategies that can increase the contribution of Sharia banking to the economy in a sustainable manner. [Penelitian ini menganalisis pengaruh total aset, total pembiayaan, dan total deposito perbankan syariah terhadap pertumbuhan ekonomi di Indonesia, yang diukur melalui Produk Domestik Bruto (PDB). Data sekunder digunakan dari kuartal pertama 2015 hingga kuartal terakhir 2023, dengan menggunakan metode Vector Error Correction Model (VECM) untuk mengidentifikasi hubungan jangka panjang dan jangka pendek antara variabel tersebut. Hasil penelitian menunjukkan bahwa total aset perbankan syariah berpengaruh positif dan signifikan terhadap PDB dalam jangka panjang, namun berpengaruh negatif dalam jangka pendek. Total pembiayaan tidak menunjukkan pengaruh signifikan dalam jangka pendek dan bahkan berdampak negatif dalam jangka panjang. Sebaliknya, total deposito berpengaruh positif signifikan terhadap PDB dalam jangka panjang. Temuan ini menyoroti pentingnya efisiensi dalam pengelolaan aset dan pembiayaan perbankan syariah serta perlunya kebijakan yang mendukung stabilitas dan kepercayaan masyarakat terhadap perbankan syariah. Kontribusi penelitian ini terletak pada penyediaan bukti empiris mengenai peran perbankan syariah dalam pertumbuhan ekonomi Indonesia, khususnya melalui analisis hubungan jangka panjang dan jangka pendek antara total aset, total pembiayaan, dan total deposito terhadap PDB. Temuan ini memperkaya literatur terkait efektivitas perbankan syariah dalam sistem keuangan nasional serta memberikan implikasi bagi kebijakan yang bertujuan meningkatkan efisiensi pengelolaan aset dan pembiayaan syariah. Selain itu, penelitian ini memberikan wawasan bagi regulator dan praktisi perbankan dalam merancang strategi yang dapat meningkatkan kontribusi perbankan syariah terhadap perekonomian secara berkelanjutan].